Specyfika zmilitaryzowanego aktora niepaństwowego we współczesnych stosunkach międzynarodowych. Przypadek Hezbollahu - Ożarowski, Rafał (Przegląd Strategiczny, 2012)
In this paper Author has defined and classified a „militarized non-state actor” pointing that this term comprises many different non-state actors like for example: political parties with their military wings, international criminal groups, terrorist organizations, private military companies or independence movements. It is also a disputable issue if armed forces deployed within governmental organizations (like theUNorNATO) are treated as militarized non-state actors or not. Lebanese Hizballah has been used here as an example to describe the specificity of a militarized non-state actor. Hizballah has its own armed forces and has been active in international relations. As a result of the analysis, such actors like Hizballah are well adoptable to new phenomena and processes which occurred in international relations, they are challenging states in their activities, moreover: they are used in many cases by states to achieve their goals. It shows the ambiguity in functioning of such a non-state actor.